Effect of Stellate Ganglion Block on Early Postoperative Insomnia of Lung Cancer - Xiangfeng WANG; Qing LIN; Lizhen LI; Haojie LU; Chuanbao XIA (康复学报)
Objective:To observe the effect of stellate ganglion block (SGB) guided by ultrasound on early postoperative insomnia of lung cancer.Methods:Sixty lung cancer patients with varying degrees of insomnia symptoms were randomly divided into the treatment group and the control group, thirty patients in each group. The control group was treated with oral 1 mg estazolam every night routinely, and the treatment group was treated with SGB for 6 days constantly besides oral drug. Patients were followed up for 4 weeks. Pittsburgh sleep quality index (PSQI) scale, total score of PSQI, each index score, sleep improved effective rate and HPA axis stress hormones were investigated before and after treatment.Results:The total effective rate of the treatment group was higher than that of the control group (P<0.05). The total score of PSQI, sleep quality, sleep efficiency, sleep disturbance, daytime function and stress hormone levels of the treatment group were significantly lower than those of the control group (P<0.05).Conclusion:SGB can reduce the early postoperative PSQI score, improve sleep quality and life quality of lung cancer patients.